2010
DOI: 10.1007/s12550-009-0040-0
|View full text |Cite
|
Sign up to set email alerts
|

Exposure of neonates to ochratoxin A: first biomonitoring results in human milk (colostrum) from Chile

Abstract: The mycotoxin ochratoxin A (OTA) and its metabolite ochratoxin alpha (OTα) were determined in milk and blood from nine lactating women who provided samples soon after delivery at a hospital in southern Chile. The analytical method applied liquid-liquid extraction with chloroform, and in the case of blood, an extra purification with solid phase extraction prior to HPLC analysis with fluorescence detection. OTA was detected in all human milk samples, with an average concentration of 106 ± 45 ng/L (range 44-184 n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
27
2
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(30 citation statements)
references
References 42 publications
(46 reference statements)
0
27
2
1
Order By: Relevance
“…The result of a similar study in Egypt indicated that from a total 120 human milk samples, OTA was found in 43 (35.8%) of the samples (22). In addition, the mean concentration of the toxin in this study was higher than that of the previous studies, such as 17.5 ng/L in Brazil (12), 10-57 ng/L in Italy (23,24), and 17-30 ng/L in Germany (16), while lower amounts such 8.87 ng/L was noticed in Egypt (25), 106 ng/L in Chile (26), 39.8 ng/L in Norway (27), and 7900 ng/L in Sierra Leone (28). …”
Section: Discussioncontrasting
confidence: 79%
“…The result of a similar study in Egypt indicated that from a total 120 human milk samples, OTA was found in 43 (35.8%) of the samples (22). In addition, the mean concentration of the toxin in this study was higher than that of the previous studies, such as 17.5 ng/L in Brazil (12), 10-57 ng/L in Italy (23,24), and 17-30 ng/L in Germany (16), while lower amounts such 8.87 ng/L was noticed in Egypt (25), 106 ng/L in Chile (26), 39.8 ng/L in Norway (27), and 7900 ng/L in Sierra Leone (28). …”
Section: Discussioncontrasting
confidence: 79%
“…For example, rat neonates exposed to OTA in only lactational milk had a 4 to 5 times higher level of OTA compared with those rats exposed only via the placenta [60]. Results of a recent biomonitoring study in Chile confirmed the presence of OTA in breast milk at levels such that the tolerable daily intake could be exceeded [75]. Of concern, in 50 lactating mothers and their infants in Egypt, the presence of OTA was associated with significantly higher levels of urine microglobulin and microalbuminuria in the infants consistent with early renal injury [76].…”
Section: Discussionmentioning
confidence: 99%
“…Antioxidants, including glutathione, are also likely to be helpful for their antioxidant and detoxification effects [23]. Vitamins A, C, E and selenium are other potentially beneficial antioxidants that may be protective in their role as superoxide anion scavengers [22, 75]. …”
Section: Discussionmentioning
confidence: 99%
“…The fetal and neonatal exposure to OTA is likely determined by the analysis of cord blood samples from pregnant women, human blood, colostrum, milk, and urine (Micco et al, 1991;Kovacs et al, 1995;Miraglia et al, 1998;Skaug et al, 1998;Muñoz et al, 2010;Klapec et al, 2012). The fetal and neonatal exposure to OTA is likely determined by the analysis of cord blood samples from pregnant women, human blood, colostrum, milk, and urine (Micco et al, 1991;Kovacs et al, 1995;Miraglia et al, 1998;Skaug et al, 1998;Muñoz et al, 2010;Klapec et al, 2012).…”
Section: Ota Biomonitoringmentioning
confidence: 99%